Net knitting instructions, Phonse Ducey's twine store, Keels, NL - Whitney, Erin (2012)
Writing on wall of Phonse Ducey's twine store in Keels, NL. Reads “KNIT 13/TAPER 14TH/KNIT TO”, instructions for putting together a fishing net of some kind.